1978
DOI: 10.2134/agronj1978.00021962007000050021x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Peanut Hulls on the Performance of Corn1

Abstract: Disposal of peanut (Arachis hypogaea L.) hulls, after separation from the seed, is a serious problem in the peanut production areas of southeastern Virginia. Limited amounts of peanut hulls are used for mulch around shrubbery, but commercial use is limited, resulting in a large volume being burned, thus contributing to the pollution hazard. Became of their chemical composition and potential use as a mulching material, it is thought that they may be of considerable importance in corn (Zea mays L.) production. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1980
1980
2016
2016

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…This value is 2 -4 fold higher than most common agricultural wastes such as rice straw, wheat straw, sugar cane bagasse and corn cob/stover [11,12]. The high lignin content of peanut shells is largely responsible for their recalcitrance to biodegradation under normal environmental conditions; for their reportedly low digestibility in ruminants [6,[20][21][22][23], and for the cost-intensive hydrolysis that is required to obtain fermentable sugars from them for bioenergy and pulp industries [12]. White rot fungi are nature's reservoir of inexpensive, environmentally friendly, complex enzymes that can selectively degrade lignin in situ, and their use for these purposes is supported in literature [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…This value is 2 -4 fold higher than most common agricultural wastes such as rice straw, wheat straw, sugar cane bagasse and corn cob/stover [11,12]. The high lignin content of peanut shells is largely responsible for their recalcitrance to biodegradation under normal environmental conditions; for their reportedly low digestibility in ruminants [6,[20][21][22][23], and for the cost-intensive hydrolysis that is required to obtain fermentable sugars from them for bioenergy and pulp industries [12]. White rot fungi are nature's reservoir of inexpensive, environmentally friendly, complex enzymes that can selectively degrade lignin in situ, and their use for these purposes is supported in literature [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…This should be beneficial in soils that limit root proliferation into subsurface horizons since seed yields of soybeans can be reduced ap-682 preciably by moisture stress during and after pod development. Lutz and Jones (1978) reported that peanut hull application increased corn (Zea mays L.) yields on a Tatum silt loam as a result of increased moisture holding capacity and increased available K. Robinson and Burdick (1978) have reported 1~hat water extracts made from the Virginia-type peanut hulls can result in lower germination (40%) and shorter shoot lengths (12 mm) for cucumber (Cucu.mis sativus L.) seedlings.…”
mentioning
confidence: 99%